The introduction of automatic blood pressure monitoring to an accident & emergency resuscitation room. Issue 1 (March 1993) - Cusack, S; Moulton, C; Swann, I J
Abstract : Machines for automatic non-invasive blood pressure (BP) monitoring are increasingly available in British accident and emergency departments. Our department recently acquired two machines with this capability for use in the resuscitation room. This provided us with an opportunity to compare the speed and frequency of automatic BP recording with the previously used manual method. We found no significant difference in either the median time to the first recording of BP or in the median number of documented recordings in the first hour. However, the overall frequency of BP recording did show a statistically significant increase. We conclude that automation alone does not improve standard practice in this area greatly.